2019
DOI: 10.1186/s12866-019-1606-4
|View full text |Cite
|
Sign up to set email alerts
|

Increase of reactive oxygen species contributes to growth inhibition by fluconazole in Cryptococcus neoformans

Abstract: Background: Cryptococcus neoformans, a basidiomycetous yeast, is a fungal pathogen that can colonize the lungs of humans causing pneumonia and fungal meningitis in severely immunocompromised individuals. Recent studies have implied that the antifungal drug fluconazole (FLC) can induce oxidative stress in C. neoformans by increasing the production of reactive oxygen species (ROS), as presence of the antioxidant ascorbic acid (AA) could reverse the inhibitory effects of FLC on C. neoformans. However, in Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“… 2018 ; Dbouk et al . 2019 ). It has been shown that co-treatment of C. neoformans with FLC and the antioxidants, retinoic acid (RA), ascorbic acid (AA) and pyrrolidine dithiocarbamate (PDTC) prevents the increase of ROS and has a significant effect by lowering the susceptibility towards FLC (Dbouk et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 2018 ; Dbouk et al . 2019 ). It has been shown that co-treatment of C. neoformans with FLC and the antioxidants, retinoic acid (RA), ascorbic acid (AA) and pyrrolidine dithiocarbamate (PDTC) prevents the increase of ROS and has a significant effect by lowering the susceptibility towards FLC (Dbouk et al .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that co-treatment of C. neoformans with FLC and the antioxidants, retinoic acid (RA), ascorbic acid (AA) and pyrrolidine dithiocarbamate (PDTC) prevents the increase of ROS and has a significant effect by lowering the susceptibility towards FLC (Dbouk et al . 2019 ). Surprisingly, the effect of yet another classic antioxidant, glutathione (GSH) had a minimal effect on susceptibility towards FLC (Dbouk et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations